2020
DOI: 10.1088/1748-9326/ab6b37
|View full text |Cite
|
Sign up to set email alerts
|

Global warming to increase violent crime in the United States

Abstract: Recent studies have revealed large and robust correlations between seasonal climate and violent crime rates at regional scales within the continental United States, begging the question of how future climate change will influence violent crime rates. Here, we combine empirical models from previous studies with 42 state-of-the-art global climate models to make such projections, while accounting for key factors like regionality and seasonality, and appropriately combining multiple of sources of uncertainty. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Grappling with the challenges to emergency medical services and pressures on Emergency Department staffing need to include extreme heat planning (e.g., van Loenhout et al., 2018 ). Challenges to public safety posed by impacts of heat waves on enhancing crime rates (Harp & Karnauskas, 2018 , 2020 ) also need consideration of staffing and training of personnel. Outdoor labor is particularly vulnerable to heat morbidity and mortality due to the nature of the work (i.e., long hours outside in the sun typically without cooling), requiring development and adherence to heat safety standards (Morrissey et al., 2021 ).…”
Section: Articlementioning
confidence: 99%
“…Grappling with the challenges to emergency medical services and pressures on Emergency Department staffing need to include extreme heat planning (e.g., van Loenhout et al., 2018 ). Challenges to public safety posed by impacts of heat waves on enhancing crime rates (Harp & Karnauskas, 2018 , 2020 ) also need consideration of staffing and training of personnel. Outdoor labor is particularly vulnerable to heat morbidity and mortality due to the nature of the work (i.e., long hours outside in the sun typically without cooling), requiring development and adherence to heat safety standards (Morrissey et al., 2021 ).…”
Section: Articlementioning
confidence: 99%
“…Extreme heat has also been found to result in increased aggression (Anderson, 2001; Butke & Sheridan, 2010) and violent behavior (Anderson, 2001; Michel et al, 2016; Rotton & Cohn, 2000, 2004; Tiihonen et al, 2017). Projections within the United States have demonstrated that the United States may experience 2.3–3.2 million more violent crimes by the end of the century depending on greenhouse gas emissions trajectories (Harp & Karnauskas, 2020).…”
Section: Introductionmentioning
confidence: 99%